Customer Relationship Management, Customer Trust, and Retention in B2B Logistics: Implications for Vocational Education - Prakoso, Budi; Hurriyati, Ratih; Gaffar, Vanessa; Sultan, Adib Mokh; Rahmiati, Filda (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study examines the mediating role of customer trust in the relationship between Customer Relationship Management (CRM) and Customer Retention within Indonesia's B2B logistics sector, specifically PT Pos Indonesia's enterprise segment, and explores implications for vocational education curriculum development in logistics programs. Method: Using a descriptive-verificative design, data were collected from 200 enterprise customers through a validated questionnaire using a 7-point semantic differential scale. CRM was measured by 13 indicators (communication, problem-solving, complaint handling), Customer Trust by 5 indicators (benevolence, integrity, competence), and Customer Retention by 4 indicators (renewal intention, switching resistance). Data analysis utilized PLS-SEM with bootstrapping (5,000 subsamples). CRM indicators were mapped against Indonesian National Qualifications Framework (KKNI) competency standards. Results: CRM significantly enhances Customer Trust (β = 0.880, t = 68.850, p < 0.001) and Customer Retention (β = 0.702, t = 12.030, p < 0.001). Customer Trust positively influences retention (β = 0.245, t = 4.361, p < 0.001) and functions as a partial mediator (β = 0.215, t = 4.440, p < 0.001). The model explains 85.4% of variance in trust and 77.5% in retention. Novelty: This study uniquely bridges industry practice and educational theory by identifying specific CRM competencies, communication quality, collaborative problem-solving, and complaint handling, that should be systematically integrated into vocational education curricula, providing evidence-based recommendations for preparing future logistics professionals.